Effect of Drought Stress on Potato Production: A Review - Muhammad Waqar Nasir; Zoltan Toth (Agronomy, 2022)
Potato is the third most consumed crop globally after rice and wheat. It is a short-duration crop, versatile in use, suitable for growing in a wide range of environments, and its production is increasing rapidly. The modern potato is considered a drought-sensitive crop, and it is susceptible to yield loss because of drought stress. Unfortunately, drought severity, frequency, and extent have been increasing around the globe because of climate change. Potato drought susceptibility has primarily been attributed to its shallow root system. However, several studies in past decades have suggested that drought susceptibility of potato also depends upon the type, developmental stage, and the morphology of the genotype, and the duration and severity of drought stress. They have been overlooked, and root depth is considered the only significant cause of potato drought susceptibility. This review combines these studies to understand the varying response of potato genotypes. This review also explores the current potato production scenario and the effect of varying degrees of drought stress on potatoes’ growth, development, and yield. In the absence of drought-tolerant genotypes, agronomic practices should be improved to mitigate drought stress. Late maturing cultivars, nutrient management, mulching, and foliar application of plant growth regulators can be used during prolonged droughts. Irrigation at tuber initiation and the tuber bulking stage during early droughts can reduce the adverse effects of drought.